The Implementation of Problem-Based Learning Model to Develop Students' Problem-Solving Abilities in Hybrid Mathematics Learning - Sianturi, Evi Yunita; Dirgantoro, Kurnia Putri Sepdikasari (STKIP Singkawang, 2023)
Based on the results of observations made and supported by previous research, it can be seen that the problem-solving ability of students still tends to be low. It can be seen that when students are presented with problem-solving problems, students are resistant and in the end unable to do the problem. Even though mathematical problem solving problems can support students' problem-solving abilities. Problem-solving skills are important as basic mathematical competencies and as provisions for everyday life. The purpose of writing this paper is to analyze the application of the PBL model in developing students' problem-solving skills in mathematics learning in a hybrid context. The subject of this study was a grade VII student at a private school in Bogor. The study used descriptive qualitative methods. The instruments used in this study include learning observation sheets, problem-solving tests, student observation sheets, and teaching reflections. The data obtained from the instrument is then processed in a simple descriptive manner, and the results are analyzed qualitatively. The results showed that the application of the PBL model was able to develop the problem-solving ability of grade VII students in mathematics learning. The PBL model is able to equip students to face the challenges of daily life by developing problem-solving skills. Therefore, the suggestion presented to the next researcher is to increase the number of meetings in applying the PBL model to gain a better conceptual understanding for students. Meanwhile, the advice addressed to teachers is to vary the problem solving, one of which is by giving group projects.